Strategies to Reduce the Risk of Central Line–Associated Bloodstream Infections in Parenteral Nutrition. Issue 2 (April 2018) - Balazh, Julia R.; Franck, Andrew J.
Abstract : Parenteral nutrition (PN) is a lifesaving or life-sustaining treatment, but complications from its use, including central line–associated bloodstream infections (CLABSIs), necessitate that care be taken to ensure its safety. Our institution developed strategies that aim to incorporate evidence-based practices to reduce the risk of CLABSIs in patients receiving PN. A retrospective evaluation was conducted to assess the implementation of these strategies. Overall, adherence to the risk-reduction strategies was high, and no patients receiving PN experienced CLABSI during the time of the study.